Ceramic assemblages of MB and LB palaces and temples: a comparative study - Samet, Inbal (Israel exploration journal, 2017)
Understanding the socio-economic importance of temples and palaces requires, in addition to an examination of their architecture, a study of the activities conducted within them. In this paper we carry out an inter- and intra-site comparison of patterns of pottery consumption in Canaanite palaces and temples during the Middle and Late Bronze Ages, in an effort to outline the socio-economic roles of these institutes. We examine three main activities that reflect these roles: the consumption of food and drink; storage; and dedication of votive, miniature vessels. We conclude that temple activities reflected in the ceramic repertoire focus on the dedication of votive vessels in the MBA and commensality in the LBA, while palaces manifest a balance between storage and food preparation and consumption, much of which is broadly similar to that of households during the Middle and Late Bronze Ages.